Experimental study of drop-panel effects on response of reinforced concrete flat slabs after loss of corner column - Qian, Kai. (2013)
Flat-slab structures—with or without drop panels—are popular construction types and have a high occupancy rate. Such flat-slab structures are more vulnerable to progressive collapse compared to beam-column-slab structures, as there are no beams that could assist in redistributing the load previously carried by the lost column. Therefore, more efforts should be taken to assess the vulnerability of flat-slab structures to resist progressive collapse. Unfortunately, few experimental studies have been conducted on this subject to date. Thus, to attain a more comprehensive understanding of the behavior of reinforced concrete (RC) flat slabs in resisting progressive collapse and to quantify the influence of the drop panel on the performance of flat slabs against progressive collapse, two series (ND and WD) of one-third-scale specimens were tested under monotonic loading to simulate axial loading in the corner column. The experimental results highlighting the behavior, such as force-displacement responses, crack patterns, and failure mechanisms, are discussed. A comparison of the performance of these two series of specimens revealed that incorporating drop panels into the flat slabs would increase the first peak-resistant capacity by up to 124.7% and significantly reduce the likelihood of progressive collapse.